Persepsi Penggemar Drama Korea Terhadap Budaya Korea: Studi Kasus Komunitas X @Kdrama_Menfess - Riana,; Kholil, Syukur (Jurnal Noken: Ilmu-Ilmu Sosial, 2024)
K-pop or Hallyu is the Korean wave, which is a feverish phenomenon ranging from music, drama, fashion, food and anything related to Korea. The entry of Korean culture into Indonesia is growing rapidly through drama series and K-pop music. Social media is very familiar among the public, social media also has a fundamental function, namely cultural transmission. Korean Popular culture is one of the results of cultural transmission which is now loved by many people. This study aims to determine the perceptions of Korean drama fans towards Korean culture through analysis of interview data with members of the @kdrama_menfess community on X social media. This research uses qualitative research methods with thematic analysis, collecting data with interview techniques, and using the Stimulus Organism Response (S-O-R) theory. The subjects studied were 10 informants from followers of the X account @kdrama_menfess who were purposively selected. The results of this study show that Korean drama fans find various interesting aspects in Korean dramas, such as interesting storylines and moments that illustrate Korean culture. The experience of watching Korean dramas also affects the way fans perceive Korean culture, with some feeling more connected to characters that reflect certain aspects of the culture.